Iconographic evidence of hybridisation between Camelus bactrianus and Camelus dromedarius at second-century AD Hatra, Iraq. (February 2022) - Vidale, Massimo; Berlioz, Stefania; Mohammed, Rowaed
Abstract: Abstract : In a sculpted frieze on a lintel of the so-called Temple of Allat at Hatra (second century AD), two rows of sitting camels converge towards a possible royal portrait. The two lead animals were previously interpreted as Bactrian camels. We reconsider this interpretation in light of recent information on ancient and contemporary practices of hybridisation between Camelus bactrianus and Camelus dromedarius.